A strategic approach for sustainable economic development for Sabah - Sarma Aralas (Penerbit Universiti Malaysia Sabah, 2024)
The study aims to assess the sustainable development goals achieved by Sabah in comparison with the other states in Malaysia. The study revealed that in terms of infrastructure, health and education, Sabah is below the national level but the poverty rate and the unemployment rate seems to be otherwise. Thus it can be concluded that strategies planning clear, manageable and measurable mechanism should be established to evaluate the effectiveness of the policy towards achieving the sustainable goals.